Idiopathic Pulmonary Fibrosis with Comorbidities at Benue State University Teaching Hospital Makurdi, Nigeria: A Report of 2 Cases with Literature Review - Mbaave, Tsavyange Peter; Chia, Daniel Msuega; Kator, Iorpagher Paul; Alye, Iwuese Benita (British Journal of Healthcare and Medical Research, 2024)
Background: Idiopathic pulmonary fibrosis (IPF) is an interstitial lung disease due to extensive lung scarring with poor prognosis that is considered rare. Few cases have been reported in Nigeria. Aim: To present 2 cases of Idiopathic Pulmonary Fibrosis occurring with comorbidities in our center. Method: A review of the case folders of 2 patients who presented with chronic dry cough and breathlessness who had radiologically confirmed diagnosis of IPF. Results: The two patients presented with dry cough. Both had clinical and High-resolution computed tomography (HRCT) evidence of Idiopathic pulmonary fibrosis.There was delay in referral and diagnostic challenges. They also had comorbidities. Treatment was given for comorbidities but no definitive treatment was available. Conclusion: We reported 2 cases of radiologically confirmed Idiopathic pulmonary fibrosis who also had comorbidities. There was delay in referral to a pulmonologist and also diagnostic challenges due non availability of the necessary diagnostic facilities. The disease may not be as rare as reported in Africa. We recommend that clinicians should be more alert to the existence of this condition and have a high index of suspicion in to be able to make early diagnosis.